The analysis of earthquake and tsunami hazards for the planned development of the Balinese cultural center in Klungkung regency - Sutarja, I Nyoman; Ardana, Made Dodiek Wirya; Fatchurohman, Iman; Aryasatya, Muhammad Maheswara (Edelweiss Applied Science and Technology, 2024)
The planned development of the Bali Cultural Center in Klungkung Regency, Bali, aims to enhance cultural tourism by creating a hub for cultural activities and information dissemination. Given the site’s susceptibility to natural hazards, particularly earthquakes and tsunamis, this research assesses the potential risks to ensure safe infrastructure development. The purpose of this study is to analyze earthquake and tsunami hazards through seismic history evaluation and modeling of ground shaking and tsunami propagation. The methodology includes seismic hazard analysis using ShakeMap software for earthquake simulations and tsunami modeling through ComMIT application, providing a comprehensive hazard assessment. Findings indicate that the area is exposed to high seismic risk, with potential shaking intensities reaching VII MMI (353 gal Peak Ground Acceleration) and tsunami inundation heights of up to 6 meters. The study concludes that these results are critical for designing resilient infrastructure and developing effective disaster mitigation strategies. Practical implications include guiding the construction of the Bali Cultural Center with a focus on disaster preparedness and risk reduction, ensuring the safety of both the infrastructure and its occupants.